2022
DOI: 10.1002/htj.22418
|View full text |Cite
|
Sign up to set email alerts
|

Use of segmental baffle in shell and tube heat exchanger for nano emulsions

Abstract: Among the heat exchangers (HE), the shell and tube type is being widely used in different applications like oil, chemical, and power plant Industries. The incorporation of segmental baffles (SB) improves the HE capacity from higher temperature fluid to lower temperature fluid. Nanofluids can be effectively used to enhance the heat transfer rate. In this study, numerical simulations have been carried out in a shell and tube heat exchanger (STHX). Among HE design methods, Tubular Exchanger Manufacturers Associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Due to the high expense of experimental setup, the numerical and theoretical works are considered to predict the results in industries at a laboratory scale. Geometrical parameters are taken from previous studies by Gugulothu et al 9,14 The adiabatic boundary condition is considered for shell wall, the mass flow rate is given as inlet from the ranging 0.23 to 0.43 kg/s at 343.15 K in shell side and 301.15 K as temperature, and 0.22 kg/s mass flow rate of tube side is given as boundary conditions at atmospheric pressure as outlet pressure on both shell and tube side. Figures 2 and 3 give some dimensions, those dimensions are given as 31.75 mm is Mustapha Mellal et al 4 Segmental baffle 09 0.640 Wilfried et al 6 Segmental baffle 92 1.650 Roetzel and Lee 7 Ahmed et al 11 Segmental baffle 37 0.500…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high expense of experimental setup, the numerical and theoretical works are considered to predict the results in industries at a laboratory scale. Geometrical parameters are taken from previous studies by Gugulothu et al 9,14 The adiabatic boundary condition is considered for shell wall, the mass flow rate is given as inlet from the ranging 0.23 to 0.43 kg/s at 343.15 K in shell side and 301.15 K as temperature, and 0.22 kg/s mass flow rate of tube side is given as boundary conditions at atmospheric pressure as outlet pressure on both shell and tube side. Figures 2 and 3 give some dimensions, those dimensions are given as 31.75 mm is Mustapha Mellal et al 4 Segmental baffle 09 0.640 Wilfried et al 6 Segmental baffle 92 1.650 Roetzel and Lee 7 Ahmed et al 11 Segmental baffle 37 0.500…”
Section: Methodsmentioning
confidence: 99%
“…As many literature papers suggested that this method is giving accurate results. The governing equations are given in Equations ( 5)- (9).…”
Section: Governing Equationsmentioning
confidence: 99%
“…The specific heat of nanofluids can be calculated by Xuan and Roetzel 23,24,26,30,31 (ρCp)normalnnormalf=(ρCp)φ(ρCp)w+φ(ρCp)p. ${(\rho {C}_{p})}_{{\rm{n}}{\rm{f}}}=(\rho {C}_{p})-\varphi {(\rho {C}_{p})}_{w}+\varphi {(\rho {C}_{p})}_{p}.$…”
Section: Thermo‐physical Properties Of Nanofluidsmentioning
confidence: 99%
“…Maxwell developed a model which is statistically applicable to homogeneous, low volume concentration single‐phase nanofluids which are uniformly sized for solid‐liquid suspensions of spherical particles. The thermal conductivity 24,30 is calculated by using an Equation (3) 31 knf=knp+mkfkf(mφφ)(kfknp)knp+mkfkf+φkfφknp, ${k}_{\mathrm{nf}}=\frac{{k}_{\mathrm{np}}+m{k}_{f}-{k}_{f}-(m\varphi -\varphi )({k}_{f}-{k}_{\mathrm{np}})}{{k}_{\mathrm{np}}+m{k}_{f}-{k}_{f}+\varphi {k}_{f}-\varphi {k}_{\mathrm{np}}},$where k f = 3.…”
Section: Thermo‐physical Properties Of Nanofluidsmentioning
confidence: 99%
See 1 more Smart Citation